Bifunctional ZIF-78 heterogeneous catalyst with dual Lewis acidic and basic sites for carbon dioxide fixation via cyclic carbonate synthesis. (December 2017) - Lin, Yi-Feng; Huang, Kai-Wei; Ko, Bao-Tsan; Lin, Kun-Yi Andrew
Graphical abstract: Highlights: Bi-functional ZIF-78 hexagonal plates were successfully prepared in the hydrothermal process. ZIF-78 hexagonal plates possessed dual Lewis acidic and basic sites for CO2 /PO cycloaddition reaction. ZIF-78 hexagonal plates serve as a heterogeneous catalyst for CO2 /PO cycloaddition reaction. ZIF-78 hexagonal plates have great potential for CO2 fixation via the syntheses of cyclic carbonates. Abstract: Zeolitic imidazole framework-78 (ZIF-78) hexagonal prisms, a combination of Zn metal and imidazolate linkers, were successfully synthesized using a facile hydrothermal process. The as-prepared ZIF-78 hexagonal prisms possessed a bifunctional property with dual Lewis acidic (Zn atom) and basic sites (-NH groups of the imidazolate linkers). This bifunctional property allowed the ZIF-78 crystals to be a potential heterogeneous catalyst in the CO2 /propylene oxide (PO) cycloaddition reaction for the synthesis of propylene carbonate (PC). To the best of our knowledge, this is the first work to use microporous ZIF-78 crystals as a catalyst for the CO2 /PO cycloaddition reaction without the addition of any co-catalyst or solvent. The effects of reaction temperature, pressure and reaction time on the PO conversion, PC selectivity and yield were also investigated in this work. The highest PC yield of 54% was obtained at a reaction temperature of 150 °C, pressure of 10 kg/cm 2 and reaction time of 15 h. Moreover, a possible mechanism of the cycloaddition reaction was also proposed in this study.